Pulse Pressure Magnifies the Effect of COMT Val158Met on 15 Years Episodic Memory Trajectories - Persson, Ninni; Lavebratt, Catharina; Sundström, Anna; Fischer, Håkan (Frontiers in Aging Neuroscience, 2016)
We investigated whether a physiological marker of cardiovascular health, pulse pressure (PP), and age magnified the effect of the functional COMT Val158Met (rs4680) polymorphism on 15-year cognitive trajectories (episodic memory [EM], visuospatial ability, and semantic memory) using data from 1585 non-demented adults from the Betula study. A multiple-group growth model was specified to gauge individual differences in change. The allelic variants showed negligible differences across the cognitive markers in average trends. The older portion of the sample selectively age-magnified the effects of Val158Met on EM changes, resulting in greater decline in Val compared to homozygote Met carriers. This effect was attenuated by statistical control for PP. Further, PP moderated the effects of COMT on 15-year EM trajectories, resulting in greater decline in Val carriers, even after accounting for the confounding effects of sex, education, cardiovascular diseases (diabetes, stroke, and hypertension), and chronological age, controlled for practice gains. The effect was still present after excluding individuals with a history of cardiovascular diseases. The effects of cognitive change were not moderated by any other covariates. This report underscores the importance of addressing synergistic effects in normal cognitive aging, as the addition thereof may even place healthy individuals at greater risk for memory decline.